The Aggregate Planning For Trucking Operation in Cikarang Dry Port - Utami, Dwi Puspita Sari; Rahmiati, Filda (School of Business and Management Institut Teknologi Bandung, 2015)
Abstract. Cikarang Dry Port currently is the only dry port in Indonesia. This Dry Port has a role to connect or extend the Sea Port to the industrial areas located far from Sea Port. Thus, it creates a value added and also reduce costs. One of the operations done in Cikarang Dry Port is trucking operation. This research aims to examine the planning of 2014 trucking activity in Cikarang Dry Port to determine the right number of the truck that will be best occupied to manage all demands. The analysis begins with demand forecasting by using a moving average method of 12 months or one year period in 2013 which will be used as main information to develop the plans. There are three plans developed in this research. Based on the three plans, Plan A with minimum trucking plan with subcontracting is the most profitable which gives the highest profitability of Rp. 374,984,625. Recommendation for this research is using the current minimum number of 39 trucks rent with additional subcontracting when the demand is exceeding the capacity, thus, Cikarang Dry Port can occupy all demands and gain more profits.Keywords: Aggregate Planning; Scheduling; Trucking Operation; Moving Average; Cikarang Dry Port